1999
DOI: 10.1111/j.1752-7325.1999.tb03236.x
|View full text |Cite
|
Sign up to set email alerts
|

Caries Experience of Urban and Rural Children in Saudi Arabia

Abstract: In Saudi Arabia, an economically prosperous developing country, exposure to cariogenic diet in urban and rural areas does not differ. Also, a difference in caries experience in urban and rural areas often reported for developing countries does not apply to Saudi Arabia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
37
0

Year Published

2002
2002
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(41 citation statements)
references
References 18 publications
4
37
0
Order By: Relevance
“…It is high time to create awareness and focus on the preventive measures in this location. [171819] Untreated caries indicates subsequent steps towards preventive and restorative care should be initiated. [2021] In order to reduce the caries prevalence, there is a need for continuous monitoring and health education to the children and parents, guardians.…”
Section: Resultsmentioning
confidence: 99%
“…It is high time to create awareness and focus on the preventive measures in this location. [171819] Untreated caries indicates subsequent steps towards preventive and restorative care should be initiated. [2021] In order to reduce the caries prevalence, there is a need for continuous monitoring and health education to the children and parents, guardians.…”
Section: Resultsmentioning
confidence: 99%
“…sumption seems to be higher than in other developing areas. 16 Studies of food habits, 17 nutritive value of the diet 19 or types of food consumption and dental caries prevalence 20,21 have been carried out in Arabian countries but to our knowledge there is no previous information about the most popular choice of items for snacks or drinks between meals amongst young children in Jordan.…”
Section: Resultsmentioning
confidence: 99%
“…22,23 Although not investigated directly in Jordan, studies of food habits, 22 of nutritive value of the diet 24 and types of food consumption in relation to caries prevalence have been carried out in neighbouring Saudi Arabia. 25,26 In younger age groups specific infant feeding habits have frequently been identified as important in both early childhood caries (ECC) and in rampant caries (severe ECC). As with other dietary practices, these habits have been related to social factors and it has been shown that the use of feeding bottles with added sugar is a major predisposing factor in the prevalence of caries in disadvantaged communities in both developing and industrialised countries.…”
Section: Introductionmentioning
confidence: 99%